Drosophila H2Av negatively regulates the activity of the IMD pathway via facilitating Relish SUMOylation. - Ruijuan Tang (Public Library of Science (PLoS), 2021)
Insects depend on the innate immune response for defense against a wide array of pathogens. Central to Drosophila immunity are antimicrobial peptides (AMPs), released into circulation when pathogens trigger either of the two widely studied signal pathways, Toll or IMD. The Toll pathway responds to infection by Gram-positive bacteria and fungi while the IMD pathway is activated by Gram-negative bacteria. During activation of the IMD pathway, the NF-κB-like transcription factor Relish is phosphorylated and then cleaved, which is crucial for IMD-dependent AMP gene induction. Here we show that loss-of-function mutants of the unconventional histone variant H2Av upregulate IMD-dependent AMP gene induction in germ-free Drosophila larvae and adults. After careful dissection of the IMD pathway, we found that Relish has an epistatic relationship with H2Av. In the H2Av mutant larvae, SUMOylation is down-regulated, suggesting a possible role of SUMOylation in the immune phenotype. Eventually we demonstrated that Relish is mostly SUMOylated on amino acid K823. Loss of the potential SUMOylation site leads to significant auto-activation of Relish in vivo. Further work indicated that H2Av regulates Relish SUMOylation after physically interacting with Su(var)2-10, the E3 component of the SUMOylation pathway. Biochemical analysis suggested that SUMOylation of Relish prevents its cleavage and activation. Our findings suggest a new mechanism by which H2Av can negatively regulate, and thus prevent spontaneous activation of IMD-dependent AMP production, through facilitating SUMOylation of the NF-κB like transcription factor Relish.